Organization Goal-Oriented Requirements Elicitation Process to Enhance Information System - Fransiskus Adikara; Bayu Hendradjaya; Benhard Sitohang (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper introduces and proposes an approach in goal-oriented requirements elicitation process that using Key Performance Indicators (KPIs), in information system enhancement process. KPIs can be used to control and reduce user requirements problems caused by personal interests of users in requirements elicitation process. An information system enhancement project for a distribution company has been used as a case study to demonstrate this approach. The case study shows that the requirements can be elicited from the organization goals and current information system condition rather than from user requirements. This approach also showed that KPIs have been able to control some user requirements that have difference point of view with high level stakeholder requirements. Compared with the previous research, IT goals and KPIs are more easily identified in the enhancement process rather than through development of a brand new information system.